Repeated measurements of cardiac troponin T and N-terminal pro-B-type natriuretic peptide to assess long-term mortality risk in subjects with osteoarthritis - Rehm, Martin; Büchele, Gisela; Brenner, Rolf Erwin; Günther, Klaus-Peter; Brenner, Hermann; Koenig, Wolfgang; Rothenbacher, Dietrich (Biomolecules, 2021)
Osteoarthritis (OA) is associated with higher cardiovascular mortality risk. High-sensitivity cardiac troponin T (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) are well-characterized prognostic cardiac markers. We aimed to describe the changes in biomarkers measured one year apart in a cohort of 347 subjects with OA who underwent hip or knee replacement surgery in 1995/1996 and to analyze the prognostic value of repeated measurements for long-term mortality. During a median follow-up of 19 years, 209 (60.2%) subjects died. Substantial changes in cardiac biomarkers, especially for NT-proBNP, and an independent prognostic value of NT-proBNP for long-term mortality were found for both baseline measurement concentration (hazard ratio (HR) 1.32, 95% confidence interval (CI) (1.13-1.55)) and follow-up measurement concentration (HR 1.39, 95% CI 1.18-1.64) (all HR per standard deviation increase after natural log-transformation). Baseline concentrations were correlated with follow-up concentrations of NT-proBNP and no longer showed prognostic value when included simultaneously in a single model (HR 1.08, 95% CI 0.86-1.37), whereas the estimate for the one-year measurement remained robust (HR 1.31, 95% CI 1.04-1.66). Therefore, no significant additional benefit of repeated NT-proBNP measurements was found in this cohort, facilitating the use of a single NT-proBNP measurement as a stable prognostic marker.
Gesehen am 08.04.2021